Sharing the costs of vocational education and training : an analysis of schemes in the newer EU Member States - (:unkn) unknown (Publications Office of the European Union, 2009)
"The study maps and compares vocational education and training (VET) cost-sharing mechanisms and regulatory instruments across the 12 newer Member States (Bulgaria, the Czech Republic, Estonia, Cyprus, Latvia, Lithuania, Hungary, Malta, Poland, Romania, Slovenia and Slovakia). It evaluates the influence of these mechanisms and instruments on private investment and participation in VET. It establishes which ones are more successful and identifies shortcomings in their governance. It also analyses the influence of contextual factors (the capacity of spending on education from public sources, the certainty of employers about their returns on investment in VET, the technological progress of the economy, and the balance of the supply and demand for labour with VET qualifications) on both cost-sharing mechanisms and regulatory instruments and on private investment and participation in VET. In combining quantitative (use of statistical data, regression analysis) and qualitative (literature review, surveys of national VET experts, qualitative comparative analysis) methods, the study reviews and evaluates the developments of these cost-sharing mechanisms and regulatory instruments in the 12 newer Member States and provides recommendations to improve VET cost-sharing policies." (Herausgeber, BIBB-Doku)
Keywords: S 4.1 Finanzierungsquellen; S 4.3 Steuerung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.2 Osteuropa; I 2.2.1 Westeuropa; Berufsbildung; Finanzierung; Bildungssteuerung; Vergleichende Berufsbildungsforschung; Qualitative Methode; Bulgarien; Estland; Lettland; Litauen; Malta; Polen; Rumänien; Slowenien; Slowakei; Tschechische Republik; Zypern